Case Report: Suprasellar Pituitary Adenoma Presenting With Temporal Lobe Seizures - Hong, Christopher S.; Gorrepati, Ramana; Kundishora, Adam J.; Elsamadicy, Aladine A.; Peter, Patricia R.; Damisah, Eyiyemisi C.; Manes, R. Peter; Omay, Sacit Bulent (Frontiers in Surgery, 2020)
Seizures in patients with pituitary pathology are uncommon and typically secondary to electrolyte disturbances. Rarely, seizures have been described from mass effect related to large prolactinomas undergoing medical treatment. We describe a 54 year-old male who presented with a first-time generalized seizure, secondary to a pituitary macroadenoma compressing the left temporal lobe. His seizures abated after endoscopic endonasal debulking of the tumor. This report highlights isolated seizures as a potential sole presenting symptom of pituitary macroadenomas without visual or endocrine dysfunction. Prompt surgical debulking to relieve mass effect on the temporal lobe may effectively prevent further seizure activity.